American response to Bangladesh liberation war - Muhith, A. M. A., 1934- (Dhaka, Bangladesh : University Press, 1996)
Chiefly documents.
Includes bibliographical references and index.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Causes -- Sources; United States -- Foreign relations -- Bangladesh -- Sources; Bangladesh -- Foreign relations -- United States -- Sources; United States -- Politics and government -- 1969-1974 -- Sources; Bengali (South Asian people) -- United States -- Politics and government -- Sources